DEVELOPMENT OF E-MODULE SCIENCE LEARNING BASED ON PROJECT BASED LEARNING TO IMPROVE CRITICAL THINKING SKILLS - Rifki Wardatul Janah; Retno Triwoelandari; Khaidir Fadil (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Critical thinking is one of the skills students must possess in the 2013 curriculum, especially in 21st-century learning. Indonesia's low ranking in PISA results in the critical thinking category, ranked 64 out of 65 countries is important from this study. The low thinking skills of students are caused by students' critical thinking skills in science learning are still not optimal. Based on observations made by researchers in the learning process, teaching materials use more books so that learning does not run interactively. This leads to students' critical thinking skills being poorly trained. This research aims to develop teaching materials in the form of project-based learning emodules that improve the critical thinking skills of grade 5 elementary school students effectively. The development method in this study uses a 4-D model from Thiagarajan (1974), namely Define, Design, Development, and Dessimination. The instruments used in this study were interviews, questionnaires, and observations. The results of this study showed that the project-based learning e-module was valid with material validation results of 75.6%, media validation results of 84.5%, and language validation results of 81.25%. In addition, student responses from individual trials were 97%, in small group trials by 90%, and in large group trials by 87%. Quantitative analysis with independent sample t-test using SPSS 26 for Windows showed that there was an average difference in final observation results between the experimental class and the control class of 2.625 with a sig (2tailed) p-value of 0.000. These results were obtained from the responses of experimental and control class students. Thus it can be concluded that the use of e-modules in learning has improved students' critical thinking.